Large Inflammatory Myofibroblastic Tumor of the Esophagus: A Case Report and Literature Review - Yamada, Hyuga; Funasaka, Kohei; Nakagawa, Mitsuru; Hirayama, Yutaka; Horiguchi, Noriyuki; Nagasaka, Mitsuo; Nakagawa, Yoshiyuki; Kuzuya, Teiji; Hashimoto, Senju; Miyahara, Ryoji; Shibata, Tomoyuki; Tachi, Yoshihiko; et al. (Internal Medicine, 2023)
Inflammatory myofibroblastic tumor (IMT) is a rare tumor composed of myofibroblasts with inflammatory blood cell infiltration. It commonly occurs in the lungs and rarely in the esophagus. We herein report a valuable case of IMT originating in the esophagus. A 60-year-old Japanese woman with dysphagia had a large subepithelial lesion in the cervical esophagus, which was 15 cm in length. Surgical resection was performed to confirm the pathological diagnosis and improve the symptoms. The postoperative diagnosis was IMT composed of multiple nodules. There was no recurrence or metastasis within one year after surgery.